2023
DOI: 10.3389/fpubh.2023.1168978
|View full text |Cite
|
Sign up to set email alerts
|

The impact of vulnerability and exposure to pervasive interprofessional incivility among medical staff on wellbeing

Abstract: IntroductionTraditional methods for modelling human interactions within organisational contexts are often hindered by the complexity inherent within these systems. Building on new approaches to information modelling in the social sciences and drawing on the work of scholars in transdisciplinary fields, we proposed that a reliable model of human interaction as well as its emergent properties can be demonstrated using theories related to emergent information.MethodsWe demonstrated these dynamics through a test c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 33 publications
(23 reference statements)
0
7
0
Order By: Relevance
“…Nearly one-third of the participants in our study reported bullying and feeling discriminated, and although there no studies specifically looking into this phenomenon particularly among our target population, there is recent systematic review of studies involving nursing students which reported workplace bullying as high as 58.2% and discrimination in the form of racism being 12.2% ( 30 ). Another study in Australia, identified uncivil and unprofessional behaviors experience by all medical staff including doctors, nurses, paramedical and support staff at workplace to be high which impacted on their wellbeing ( 31 ). Our study showed that bullying/harassment had negative impact on participants but this association did not reach statistical significance ( p = 0.063) while experiencing discrimination did not have any impact on burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Nearly one-third of the participants in our study reported bullying and feeling discriminated, and although there no studies specifically looking into this phenomenon particularly among our target population, there is recent systematic review of studies involving nursing students which reported workplace bullying as high as 58.2% and discrimination in the form of racism being 12.2% ( 30 ). Another study in Australia, identified uncivil and unprofessional behaviors experience by all medical staff including doctors, nurses, paramedical and support staff at workplace to be high which impacted on their wellbeing ( 31 ). Our study showed that bullying/harassment had negative impact on participants but this association did not reach statistical significance ( p = 0.063) while experiencing discrimination did not have any impact on burnout.…”
Section: Discussionmentioning
confidence: 99%
“…Recent research suggests that vulnerability to UB (i.e. likelihood of nega�ve impact to wellbeing) among doctors increases with greater exposure to UB, being female, and under 55 years of age [32]. The group most affected by UB, and why this may be the case, are outlined in this sec�on.…”
Section: Who Is Most Affected By Ub?mentioning
confidence: 94%
“…Experiencing UB has been associated with a greater incidence of burnout [30], inten�on to leave and absences from work [31], and in severe cases, suicidal idea�on [22]. An analysis of survey data from 512 medical staff in seven Australian hospitals found staff who were exposed to rudeness more frequently became more vulnerable to it, and that being a woman, working at a public hospital, or having a lower professional status, could worsen this vulnerability [32]. Individuals bear the brunt of the impact of UB, yet, cumula�vely, these impacts also affect the organisa�ons in which they work.…”
Section: Introduc�onmentioning
confidence: 99%
“…Recent research suggests that vulnerability to UB (i.e. likelihood of negative impact to wellbeing) among doctors increases with greater exposure to UB, being female, and under 55 years of age (32).…”
Section: How Do Unprofessional Behaviours Impact Patient Safety?mentioning
confidence: 99%
“…Experiencing UB has been associated with a greater incidence of burnout (30), intention to leave and absences from work (31), and in severe cases, suicidal ideation (21). An analysis of survey data from 512 medical staff in seven Australian hospitals found staff who were exposed to rudeness more frequently became more vulnerable to it, and that being a woman, working at a public hospital, or having a lower professional status, could worsen this vulnerability (32). Individuals bear the brunt of the impact of UB, yet cumulatively, these impacts also affect the organisations in which they work.…”
Section: Introductionmentioning
confidence: 99%